Effect of training on zinc metabolism: changes in serum and sweat zinc concentrations in sportsmen - Cordova, A.; Navas, F. J. (Annals of Nutrition and Metabolism, 1998)
The purpose of this research was to determine the effects of daily physical training on serum and sweat zinc concentrations in professional sportsmen between October and December, during the competing season. Twelve volleyball players and another 12 control subjects have participated in this study. Tests were made in October and December which consisted of a progressive bicycle ergometer test (increasing 30 W every 3 min to reach maximum tolerated power). Blood samples were obtained at rest and immediately after exercise. Total serum zinc increased significantly after maximal exercise in both sportsmen and control subjects. In athletes, the change after exercise was significantly higher in December than in October. The percentage of ultrafiltrable zinc (ZnUf) in October was similar in sportsmen and in controls. In December, however, after exercise, the percentage of ZnUf was higher in athletes. With respect to sweat zinc, it was in the same range both in controls and in sportsmen in October. In December, however, sweat zinc was significantly higher in athletes as compared with the situation in October and with respect to the control group. In October, the zinc concentration of urine was similar for sportsmen and controls. In December, the sportsmen showed an increase in urinary zinc excretion with respect to control subjects. Cortisol in athletes increased significantly after exercise in December. In conclusion, a daily and maintained practice of exercise is probably responsible for an alteration of zinc metabolism. The results suggest that ZnUf control, zinc supplementation and/or stress control appear to be indicated in athletes to prevent the diminution of active ZnUf. In our practical opinion we think that alterations in zinc metabolism with increases in zinc excretion and stress levels lead to a situation of latent fatigue with a decreased endurance.